PENGENDALIAN PERSEDIAAN MATERIAL BESI HOLLOW MENGGUNAKAN METODE EOQ, POQ, DAN JIT DI TOKO SUMBER BANGUNAN JAYA GORONTALO - Moh Wahyudin P Sunarto; Trifandi Lasalewo; Hendra Uloli (Jurnal Ilmu Teknik Terapan, 2025)
This research aims to determine the optimal inventory control method used by the Sumber Bangunan Jaya Gorontalo Store by comparing the policies implemented by the company with three inventory methods, namely Economic Order Quantity, Periodic Order Quantity and Just In Time. The data collection techniques used in this research were observation, documentation and interviews. The data analysis methods used in this research are EOQ formula, Safety Stock, Reorder Point, POQ Formula and Just In Time Formula. The research results show that the EOQ and JIT systems are more efficient compared to the company inventory system and POQ